Nile River clayey materials in Sudan: Chemical and isotope analysis as reference data for ancient pottery provenance studies. (30th May 2023) - Maritan, Lara; Gravagna, Elisa; Cavazzini, Giancarlo; Zerboni, Andrea; Mazzoli, Claudio; Grifa, Celestino; Mercurio, Mariano; Mohamed, Abdelrahman Ali; Usai, Donatella; Salvatori, Sandro
Abstract: This research aims to define a chemical, mineralogical and strontium isotope database for clayey materials collected along the Nile River banks (White Nile, Blue Nile, Atbara and Main Nile Rivers) in Sudan, to be use for prehistoric and historic pottery provenance studies. The approach here adopted consists in using the clayey materials tout court, without any pre-treatment, such as the depuration from the sand- and silt-sized fractions, in order to maintain unaltered the mineralogical and geochemical features of the natural resources possibly available also in ancient times for the pottery production, thus avoiding any possible preparation bias. Results indicate that sediments along different sections of the Nile River display characteristic geochemical and strontium isotopic signature, representing an important discrimination tool applied to ancient ceramics provenance and human mobility studies.